ANALISIS PENGARUH KESADARAN MEREK, PERSEPSI KUALITAS DAN LOYALITAS MEREK TERHADAP NILAI PELANGGAN MOBIL MEREK TOYOTA - Herma Yunitasari; Ahyar Yuniawan (Faculty of Economics and Business Diponegoro University, 2012)
ABSTRACT Consumers will always consider any benefits they would receive or costs they would have to pay when they want to buy a product. This critical consideration happen as the information dissemination that using information technology has made them to be more careful when they received product offers. In this situation, product quality is relatively depend on the consumer’s judgement or the value that expected by customer. As consequence, producer must give strong consideration on customer value (Eka, 2001) in which value would be created through brand, process and service (Kertajaya, 1994 in Irawan, 1995). The study was aimed to find the significant impact of brand awareness, quality perception and brand loyalty on customer value. The survey method was employed in this study. The respondents would ones who have car on their own and used it for at least one year. All items in this survey were adopted from several scholars in Baldauf et al. (2003). Linear regression analysis was used to test the hypothesized model statistically to determine the extent to which the proposed model is consistent with the sample data. The study results showed that all variables have significant effect to customer value. Hypothesis tests has showed that brand loyalty has the biggest (33.5%) effect on customer value which followed by quality perception (32.1%) and brand awareness (29.1%). It could be conclude that all independent variable partially has significant impact on customer value. F test also showed a significant value (34.794). It seemed that this research showed vary good results where the sample data has significant support to the proposed model. The study results could be taken into account to determine any policies that link the all variables which were have taken into account. Keywords: customer value; survey method; linear regression analysis